Denmark : Financial Sector Assessment Program; Detailed Assessment of Observance of the Basel Core Principles. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Detailed Assessment of Observance of the Basel Core Principles for Denmark. The assessment reveals that the basic legal framework is contained in the Financial Business Act (FBA), and in executive orders and explanatory guidelines issued pursuant to the FBA. These provide powers for the Danish Financial Supervisory Authority to supervise all financial institutions. Legal protection for supervisors is currently not provided for in specific legislation but general legislative arrangements ensure that staff is protected against lawsuits while discharging their duties in good faith.